Balancing Eating With Breathing: Community-Dwelling Older Adults' Experiences of Dysphagia and Texture-Modified Diets. (12th January 2017) - Seshadri, Sandhya; Sellers, Craig R; Kearney, Margaret H
Abstract: Purpose: Although many older adults suffer from dysphagia and are required to eat texture-modified diets, little is known about the experiences and challenges faced in doing so at home. In this study, we explored the perspectives of community-dwelling older adults as they struggled to balance dysphagia symptoms and recommended diet modifications with their preferred lifestyles. Design and Methods: Using an interpretive descriptive design, we conducted 37 in-home semi-structured interviews and 5 member-checking interviews, participant observations during a meal, and reviewed the medical charts of 20 participants recruited through maximum variation purposeful sampling. Meaning units and codes were identified and synthesized into 4 themes. Results: Participants faced a frightening choice between eating and breathing. Hiding dysphagia symptoms from the public eye was important to preserve self-identity. Following the recommended diet created a feeling that life was "falling apart." We also found that adhering to the diet was not an "all or none" phenomenon. Implications: Given that correct adherence to the restrictive diet is rare, to effectively manage dysphagia symptoms, clinicians must appreciate the full range of impact of dysphagia and texture-modified diets on the lives of older adults.